Organization planning manual - Famularo, Joseph J. (New York : Amacom, 1979)
This volume represents an updating of the original publication. In this book, organizations plans include a discussion of organization charts, the development of position descriptions, typical statements of company objectives and policies, and a glossary of standard terms commonly used in organization planning.
Includes bibliographical references.
hza 18/07/2018
Loan
Keywords: Organization charts; Job descriptions; Communication in management; Business planning